Microstructure and anisotropic tensile performance of 316L stainless steel manufactured by selective laser melting (Fracture and Structural Integrity, 2022)
The selective laser melting (SLM) technology is widely used to manufacture 316L stainless steel (SS) components for industrial applications. To understand the microstructure and the mechanical properties of additively manufactured 316L alloy, bulk materials were fabricated in longitudinal and transverse directions from which subset tensile specimens were then machine. Bulk materials were subjected to porosity detection with X-ray computed tomography and texture analysis with electron backscatter diffraction (EBSD). Microstructural investigations reveal that the SLM-built specimens had a porosity of 1.87%, and a preferential {110} orientation parallel to the build direction. The transverse specimens show significantly better properties in elastic modulus E (215.1±4.7GPa), yielding stress σy (548.2±8.3MPa) and ultimate tensile strength UTS (705.6±2.9MPa) than the longitudinal ones (E of 175.9±9.8GPa, σy of 495.3±15.5 and UTS of 608.8±3.6MPa). The anisotropic mechanical performance was attributed to the preferential {110} texture caused by thermal conditions during manufacturing and the embedded voids due to insufficient melting. A three-parameter Weibull distribution was adopted to further describe the mechanical anisotropy of SS316L based on stochastic experimental measurements. Fractography indicated the existence of manufacturing defects drive to premature failure of SS316L specimens—around half SS316L specimens failed of elongation less than 0.4.
Keywords: Selective laser melting; 316L stainless steel; porosity; mechanical anisotropy; Weibull distribution